Do Floods have Permanent Effects? Evidence from the Netherlands - Trond G. Husby; Henri L.F. de Groot; Marjan W. Hofkes; Martijn I. Dröes (Tinbergen Institute, 2013)
This study investigates the short- and long-run impact on population dynamics of the major flood in the Netherlands in 1953. A dynamic difference-in-differences analysis reveals that the flood had an immediate negative impact on population growth, but limited long term effects. In contrast, the resulting flood protection programme (Deltaworks), had a persisting positive effect on population growth. As a result, there has been an increase in population in flood prone areas.
Keywords: H12; J10; N34; Q54; R23; 330; regional population dynamics; natural disasters; flood risk management